المسجد وإشعاعه الدعوي والتعليمي –مسجد الكوثر ولاية الوادي نموذجا- - ميسه, راضية; عياشي, عمر جيهان; عيساوي, كلثوم; عموري, إسلام (جامعة الوادي university of eloued, 2020)
لقد تناولنا في د ا رسة هذا البحث مفهوم المسجد وإطاره التنظيمي ،فتطرقنا إلى ذكر أهم مساجد ولاية الوادي وبيان نشاطاتها الدعوية ،كما تكلمنا عن مسجد الكوثر بحي الكوثر الوادي وذكر إسهاماته الدعوية والتعليمية من خلال الدروس والخطب ،وذكرنا الأئمة والمؤذون الذين تداولوا على المسجد وخدمته، وتحدثنا على تعليم الق ا رن بالمسجد وأهم المحاض ا رت والندوات والفتوى وإصلاح ذات البين وعقود الزواج والتبرعات والمساعدات وبعض من نماذج الخطب التي ألقاها أئمة المسجد. Summary: In the study of this research, we dealt with the concept of the mosque and its organizational framework, so we also touched on mentioning the most important mosques in the wilayat of the valley and explaining their da'wah activities, as we talked about the Al-Kawthar mosque in the Al-Kawthar Valley neighborhood and mentioned its advocacy and educational contributions through lessons and sermons, and we mentioned the imams and muezzins who circulated the mosque and its service, and we talked On teaching the Qur’an in the mosque, the most important lectures, seminars, and fatwas, reforming the same, marriage contracts, donations, aids, and some examples of speeches delivered by the imams of the mosque.
دعوة